cON/FFlating spaces: on the intersections and conflation of our ONline and OFFline worlds - Bork-Hüffer, Tabea (Transient spaces blog, 2019)
When did you last schedule an offline meeting with friends without social media, navigate through an unknown physical location without a digital navigation system, relocate to a new place without previously obtaining information on it from online sources? Digital devices, media, and data have become pervasive features of the lives of many of us. What we are yet missing is a terminology that describes these (to varying degrees) interdependent, entangled, and CONFLATED ONline and OFFline spheres. Together with Brenda Yeoh (Bork-Hüffer and Yeoh 2017: 93) I suggested cON/FFlating situational spaces as a conceptual bridge for describing the increasingly inseparable intersections of the two spheres, and the spaces that emerge thereof.